The effectiveness of the housing facilities provided to student in Kolej Kediaman Indah Permai Universiti Malaysia Sabah / Joehan Joehari William - Joehari William, Joehan (2006)
A study entitled "The Effectiveness Of The Housing Facilities Provided To Student In Kolej Kediaman Indah Permai, Universiti Malaysia Sabah" is proposed to focus on the effectiveness facility on satisfying the students in the higher education level. In achieving the effectiveness facility, the students often need to actively participate in the production of facility and such participation needs to be encouraged and guided. This research examined the effectiveness of these investments on the housing facilities that have been made by the Universiti Malaysia Sabah thought the respond that the student give to the Universiti and also the Universiti aim is to being assess the facilities for long-term effectiveness not just satisfaction shortly after completion. The study also wants to get the clear picture of the effectiveness of the housing facilities in Kolej Kediaman Indah Permai and also to formulate new strategies on improving the housing facilities effectiveness. From this study, it was found that 136 students agree that the housing facilities that been provided by the Kolej Kediaman Indah Permai are effective for giving comfortable studying environment for student and only 14 student do not agree the housing facilities that been provided by the Kolej Kediaman Indah Permai are effective for giving comfortable studying environment for student. This result shows that the Housing Facilities that been provided to student in Kolej Kediaman Indah Permai, Universiti Malaysia Sabah are effective on giving comfortable studying environment to the student.